Stunting and Its Determinants among Children Aged 6–59 Months in Northern Ethiopia: A Cross-Sectional Study. (25th June 2018) - Abeway, Shiferaw; Gebremichael, Bereket; Murugan, Rajalakshmi; Assefa, Masresha; Adinew, Yohannes Mehretie
Abstract : Background . Stunting reflects chronic undernutrition during the most critical periods of growth and development in early life. The study was aimed at assessing the magnitude of stunting and associated factors among children aged 6–59 month in central Ethiopia. Methods . A community-based cross-sectional study was conducted among 410 children aged between 6 and 59 months. Systematic random sampling technique was employed to select study participants. Interviewer-administered structured questionnaire was used to collect data. The data were entered using EPI INFO version 3.5.1, and analysis was done by SPSS version 21 and ENA, 2007 software for anthropometric calculation. World Health Organization standard 2006 was used to analyse anthropometric data. Bivariate and multivariable logistic regression analyses were also carried out to identify predictors of stunting. Statistical significance was declared atp < 0.05 and 95% CI. Results . Overall magnitude of stunting was 52.4 (95% CI: 47.6–57.2). Being female (AOR: 2.8, 95% CI: 1.503–5.099), belonging to age group of 25–59 months (AOR: 4, 95% CI: 1.881–8.424) and birth weight of <2.5 kg (AOR: 5, 95% CI: 1.450–17.309), mothers' lack of ANC visits (AOR: 3.2 95% CI: 1.40–7.10), and mistimed complementary feeding initiation (AOR: 2.4, 95% CI: 1.266–4.606) were positively associated with child stunting, whereas educational status of the mother (AOR: 0.01, 95% CI: 0.001–0.063) showed negative association. Conclusion . Stunting was a highly prevalent problem in the study area. Low weight at birth, female sex, older age, mistimed initiation of complimentary feeding, and mothers' lack of ANC visit were found to have significant relation with children's chronic malnutrition. Thus, interventions shall effectively address those factors to alleviate the problem.